Los vinos ibéricos en Roma (y Ostia) en el Medio Imperio (siglo II ‒ principios del III d. C.). Análisis y revisiones de datos - Radaelli, Edoardo (Rzym a Półwysep Iberyjski: Różnorodność relacji od starożytności po współczesność, 2019)
The excavations in the building known as the Terme di Elagabalo in Rome revealed large amounts of fragments. The amounts of Iberian wine-amphorae found in the Middle Imperial contexts of this site (2nd – early 3rd centuries AD) will be added to those found in other excavations carried out in Rome and Ostia in order to ponder over their presence in both cities during this period. Also, ancient sources will be analyzed so as to identify the quality of these wines (including also the defrutum), leading to a reflection (with theories derived from social sciences) regarding their consumers.